In Jammu Region Cultivation of apple is profitable - Sharma, Akash; Wali, V K; Gupta, Vishal; Sharma, Satish; Sharma, Rohit (Indian Horticulture, 2019)
The apple, is the pomaceous fruit of the apple tree, species Malus domestica in the rose family (Rosaceae). It is one of the most widely cultivated fruit trees and the most widely known of the many members of genus Malus that are used by humans. The apple is the most ubiquitous of temperate fruits and has been cultivated in Europe and Asia from antiquity. Apple may be eaten off the tree or stored up to a year. Apple can be processed into sauce, slice, or juice and are favoured for pastries, cake, tarts, and pies. The pulp has been processed into candies (fruit leathers) and used as a source of pectin. The juice can be consumed fresh, either natural or filtered, fermented into alcoholic beverages such as cider or wine, distilled into brandy, or transformed into vinegar. Research and extension activities related to its cultivation are the need of the hour for increasing the production and popularizing its cultivation in the potential zones of the country.